The Matrix Revolutions Disc 1-2 - Wachowski, Andy.; Francine, Bell.; Helmut Bakaitis; Kate Beahan; Monica Bellucci; Rachel Blackman; Tanveer K Atwal; Mary Alice; Wachowski, Larry (USA Warner Bros. Pictures, 2003)
The machine army continues to drill towards Zion. Within hours, they will overrun the population of the Zionites and lay extinction to human kind. Meanwhile, Neo is held captive by the Merovingian at a train station. Trinity & Morpheus set out on a journey to release him from a mysterious train operator. Also, Smith resumes his quest to kill ""Mr. Anderson"" as he reveals his identity into the real world and resumes to replicate his program inside the system of The Matrix, causing it to decay. All hope is placed in the freed Neo, who must travel to the city of the machines in the Logos ship with Trinity and bargain to save each kingdom from destruction by finishing Smith once and for all. But even with his new powers over the sentinels, will he be able to fight them off?
The human city of Zion defends itself against the massive invasion of the machines as Neo fights to end the war at another front while also opposing the rogue Agent Smith.
Andy Wachowski
Languages : English, Turkish Subtitles : English, Turkish
Keywords: SciFi; Thriller; Action